If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15+(-4x-18)=9
We simplify the equation to the form, which is simple to understand
15+(-4x-18)=9
Remove unnecessary parentheses
+15-4x-18=+9
We move all terms containing x to the left and all other terms to the right.
-4x=+9-15+18
We simplify left and right side of the equation.
-4x=+12
We divide both sides of the equation by -4 to get x.
x=-3
| 5n-7=3n-9 | | a/-6+8=12 | | 1-k=27 | | c/4=8 | | d/-2+5=7 | | 16-(9b+3)=4 | | 2(x-2)=16-3x | | -7x+y=-4 | | (2s+4)(2s-4)= | | 7x^2-5=2 | | x/4+10=34 | | 6x-2=-4x+7 | | -9=-20+a | | 17=2x-9 | | 4(x-2)+5x=10 | | 45/450 | | 31=3-4x | | 1+2x-3-4x-5=6 | | 3x/1=2x | | 5*10/4 | | 2(x+4)+5x=50 | | 5n+8=3n | | logs(4x-18)-logs(x-6)=1 | | 3.8=p/3-7.2 | | y/4=5+1 | | 6(x+3)=18 | | (4x-18)-logs(x-6)=1 | | ((x-2x)+2x(y+10xy))=0 | | (-31)(11)= | | 19x+(-4x+3)=2 | | 3*x-6=2*x+8 | | 4x/2+9 |